(untitled) - Bohm, Robert M. (Princeton, N.J., 2007)
This book introduction to criminal justice in the United States has been ... updated and revised to include coverage of criminal justice's new, expanded role in the war on terrorism as well as to incorporate other recent developments, cases, and research in the field.
Keywords: Criminal justice, Administration of,Cục Tư pháp hình sự; United States